ПРИНЦИП «КІЛЬКІСТЬ — ЯКІСТЬ — ВАРТІСТЬ ПОСЛУГ»: ЕКОНОМІКО-ПРАВОВІ УМОВИ РЕАЛІЗАЦІЇ У ЖИТЛОВО-КОМУНАЛЬНІЙ СФЕРІ МІСТА - Melnykova, M.V.; Hradoboyeva, Ye.S. (Економіка та право, 2019)
The principle of "quantity — quality — cost of services" in the housing and communal sphere of the city and the conditions for its realization in this article was considered. The features of the housing and communal sphere of the city were determined, which determine the quantitative, qualitative and cost characteristics of housing and communal services. The factors of positive and negative impact on the quantity and quality of housing and utilities were systematized. The economic and legal principles of setting tariffs for housing and communal services provided to residents of Uk raini an cities were generalized. The legislative, regulatory and legal framework for adjusting the cost of services depending on their actual quantity and quality was analyzed. The essence of the concept of "utility value of utility services" was described, which is the basis for the implementation of the principle "quantity — quality — cost of services". This principle is to achieve the optimum ratio "price (tariff) / cost", and requires consideration of factors that affect its implementation. The conditions for observance of the principle "quantity — quality — cost of services" in the housing and communal sphere of Ukrainian cities were determined. The particular attention was paid to implementing innovations for improving of the quality of water, electricity, gas and waste management services. The state of innovative activity of municipal enterprises providing utilities was analyzed. According to the results of the analysis, the low level of innovation implementation was determined, which negatively influences the implementation of the principle "quantity — quality — cost of services" and makes it impossible to ensure the optimal ratio "price (tariff) / cost". In this regard, the necessity of increasing the amount of funding from the local budget of innovative development projects, the introduction of resource-saving and energy-efficient technologies, as well as the modernization of communal infrastructure were justified. The role of associations of co-owners of apartment buildings (ACMHs) and management companies (managers of apartment buildings) in controlling the quantity, quality and cost of providing residential and communal services to consumers was emphasized. Further researches require the issue of economic and legal support for claim work by condominiums and management companies. REFERENCES1. Derzhavna sluzhba statystyky Ukrainy. Ofitsiinyi sait. 2019. URL: http://www.ukrstat.gov.ua [in Ukrainian].2. Serbinova K.Kh. Taryfna polityka ta pidvyshchennia efektyvnosti miskoho hospodarstva. Sciencer of Europe — Praha. 2016. No. 2 (2), vol. 1. P. 35-38 [in Ukrainian].3. Bryl P.O. Doslidzhennia zarubizhnoho dosvidu publichnoho upravlinnia zhytlovo-komunalnym hospodarstvom. Investytsii: praktyka ta dosvid. 2018. No. 4. P. 142-146 [in Ukrainian].4. Danylyshyn B.M., Pylypiv V.V. Detsentralizatsiia u krainakh YeS: uroky dlia Ukrainy. Rehionalna ekonomika. 2016. No. 1. P. 5-11 [in Ukrainian].5. Berezhna A.Iu., Kolontaievskyi O.P. Formuvannia osnov upravlinnia spozhyvchoiu loialnistiu zhytlovo-komunalnoho hospodarstva. Komunalne hospodarstvo mist. 2016. Iss. 129. P. 39-45 [in Ukrainian].6. Salukvadze I.M. Spozhyvchyi rynok zhytlovo-komunalnykh posluh: rehionalnyi aspekt. Molodyi vchenyi. 2015. No. 2 (17). P. 37-40 [in Ukrainian].7. Brazhnikova L. Tsinovyi chynnyk ekonomichnoi povedinky vyrobnykiv zhytlovo-komunalnykh posluh. Halytskyi ekonomichnyi visnyk. 2012. No. 3 (36). P. 66-75 [in Ukrainian].8. Modernising municipal infrastructure in Central and Eastern Europe in the context of EU environmental policy. Schriftenreihe des Zentrums für Internationale Wirtschaftsbeziehungen der Universität Leipzig. Ed. by Cornelie Kunze and Thomas Lenk. 2009. Vol. 26. 133 р. URL: https://www.dbu.de/OPAC/ab/DBU-Abschlussbericht-AZ-24550_19.pdf9. Topping R., Lawrence T., Spencer Ju. Organizing Residential Utilities: A New Approach to Housing Quality. November 2004. 80 p. URL: https://www.huduser.gov/portal/Publications/pdf/DisentanglingUtilities.pdf10. Addressing Affordability of Utility Services in Urban Housing: Energy Efficiency Solutions. Regional Synthesis Paper. October 2007. 94 р. URL: https://www.ase.org/sites/ase.org/files/residential_ee_study_final.pdf11. Ukraintsiam vstanovyly maksymalnyi rozmir abonplaty za ZhKP. Ukraina Komunalna. 2019. URL: http://jkg-portal.com.ua/ua/publication/one/ukrajincjam-vstanovili-maksimalnij-rozmr-abonplati-za-zhkp-57319 [in Ukrainian].12. Novytskyi D. Stymuliuiuche taryfoutvorennia maie staty diievym mekhanizmom zaluchennia koshtiv dlia hlobalnoi zaminy merezh. 2019. URL: https://www.vodokanal.kiev.ua/ua/news/2017-11-09-stimylyuyuche-tarifoytvorennyama-stati-dvim-mehanzmom-zalychennya-koshtv-dlya-globalno-zamni-merezh-novitskij [in Ukrainian].13. Zubko H. Dokhody mistsevykh biudzhetiv za I pivrichchia 2019 roku zrosly do 129 mlrd. hrn. Ofitsiinyi sait Ministerstva rehionalnoho rozvytku, budivnytstva ta zhytlovo-komunalnoho hospodarstva Ukrainy. 2019. URL: http://www.minregion.gov.ua/press/news/dohodi-mistsevih-byudzhetiv-za-i-pivrichchya-2019-roku-zrosli-do-129-mlrd-grn-zubko/ [in Ukrainian].